Development of Mathematics Learning Media Based on Assemblr Edu in Primary Schools - Muslimatin, Evia; Novitasari, Meggy (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to develop and implement Assemblr Edu-based learning media to increase the learning interest of fourth-grade students at SDIT Nur Hasan. Methodology: The research uses a qualitative approach, with data collected through observation and interviews conducted at SDIT Nur Hasan. The focus is on analyzing the impact of Assemblr Edu media on student engagement and interest. Results: The implementation of Assemblr Edu learning media proved effective in enhancing students' learning interest. Data analysis indicated an average increase of 81% in students' enthusiasm and participation after using the media. The media was deemed highly feasible and suitable for classroom application. Applications/Originality/Value: This research highlights the potential of augmented reality-based platforms like Assemblr Edu as an innovative and engaging tool to foster learning interest in elementary education. Its success at SDIT NUR HASAN during the 2023/2024 academic year demonstrates its relevance for broader application in similar educational settings.